Stabilization of β-Carotene Liposomes with Chitosan–Lactoferrin Coating System: Vesicle Properties and Anti-Inflammatory In Vitro Studies - Shuxin Gao; Xiangzhou Yi; Xia Gao; Zhengsen Long; Jingfeng Guo; Guanghua Xia; Xuanri Shen (Foods)
Liposomes serve as an effective delivery system capable of encapsulating a variety of bioactive substances. However, their structural integrity is susceptible to damage from various environmental factors, which can result in the leakage of the encapsulated bioactive agents. Consequently, identifying effective strategies to enhance the stability of liposomes has become a central focus of contemporary liposome research. Surface modification, achieved by introducing a protective layer on the liposome surface, effectively reduces liposome aggregation and enhances their stability. To this end, we designed a surface modification and constructed liposomes loaded with β-carotene through co-modification with chitosan and lactoferrin, resulting in enhanced stability. This improvement was evident in terms of storage stability, light stability, and in vitro digestion stability. The study investigated the morphology, structure, and physicochemical properties of liposomes with varying degrees of modification. CS-LF co-modified liposomes exhibited significant structural changes, with particle size increasing from 257.9 ± 6.2 nm to 580.5 ± 21.5 nm, and zeta potential shifting from negative to +48.9 ± 1.3 mV. Chitosan and lactoferrin were modified on the liposome surface through electrostatic interactions and hydrogen bonding, forming a dense protective barrier on the lipid membrane. Physicochemical analysis indicated that chitosan–lactoferrin co-modification led to a more ordered arrangement of the phospholipid bilayer, reduced membrane fluidity, and increased membrane rigidity. The interactions between chitosan, lactoferrin, and phospholipids were enhanced through hydrogen bonding, resulting in a denser surface membrane structure. This structural integrity reduced membrane permeability and improved the stability of liposomes under storage conditions, UV irradiation, and in vitro digestion. Additionally, co-modified chitosan–lactoferrin liposomes effectively alleviated lipopolysaccharide-induced inflammatory damage in mouse microglial cells by increasing cellular uptake capacity, thereby enhancing the bioavailability of β-carotene. The results of this study demonstrate that chitosan–lactoferrin co-modification significantly enhances the stability of liposomes and the bioavailability of β-carotene. These findings may contribute to the development of multi-substance co-modified liposome systems, providing a more stable transport mechanism for various compounds.